Una polèmica sobre la llengua literària - Salvador, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: A study of the journalistic controversies in 1908 and 1909 about the literary language of Valencian writers. The participation of outstanding men of letters and the discursive mechanism of the controversy give to this fact an interest that goes beyond its value as a mere sociolinguistic document.